Campylobacter fetus spondylodiscitis: A case report and review of the literature. (2018) - Olaiya, Daniel; Fok, Rosemary; Chakrabarti, Prithwiraj; Sharma, Himanshu; Greig, James
Abstract: Campylobacter are common zoonotic food borne pathogens but infrequent causes of disseminated human infection. Campylobacter fetus is an unusual cause of human infection and spondylodiscitis. We describe a case of C. fetus infection in a 72-year-old woman who presented with indolent onset lumbar spondylodiscitis. The literature is reviewed and the presentation of spondylodiscitis is contrasted with the usual aggressive nature of bacteremia with this pathogen.